2016
DOI: 10.1117/1.oe.55.5.053109
|View full text |Cite
|
Sign up to set email alerts
|

Patterned fabric defect detection via convolutional matching pursuit dual-dictionary

Abstract: Patterned fabric defect detection via convolutional matching pursuit dual-dictionary," Opt. Eng. 55(5), 053109 (2016), Abstract. Automatic patterned fabric defect detection is a promising technique for textile manufacturing due to its low cost and high efficiency. The applicability of most existing algorithms, however, is limited by their intensive computation. To overcome or alleviate the problem, this paper presents a convolutional matching pursuit (CMP) dual-dictionary algorithm for patterned fabric defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This method has a good effect on the defect detection of raw fabric. Jing et al [24] proposed a convolutional matching pursuit dual-dictionary algorithm for patterned fabric defect detection. Dual-dictionary and sparse coefficients of the defect-free sample set are obtained via convolutional matching pursuit and the Ksingular value decomposition based on a Gabor filter.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has a good effect on the defect detection of raw fabric. Jing et al [24] proposed a convolutional matching pursuit dual-dictionary algorithm for patterned fabric defect detection. Dual-dictionary and sparse coefficients of the defect-free sample set are obtained via convolutional matching pursuit and the Ksingular value decomposition based on a Gabor filter.…”
Section: Related Workmentioning
confidence: 99%
“…In the experiment, TILDA [24][28] fabric sample database is used to test our proposed algorithm. TILDA fabric sample database is a standard fabric defect sample database, which contains two groups of fabric samples C1 and C2.…”
Section: A Performance On Raw Fabric Defect Detectionmentioning
confidence: 99%
“…Jing et al [11] proposed a convolutional matching pursuit (CMP) dual-dictionary method for patterned fabric defect detection. A set of defect-free image blocks are selected as a sample set by sliding window.…”
Section: Related Work a Fabric Defect Detectionmentioning
confidence: 99%
“…These methods work well for simple plain and twill fabric images, but not for fabric of complex texture, and hence they can not be directly applied to patterned fabrics. The second category of methods are for fabric image with patterned texture, as shown in Fig 1(b), including Elo rating method [9], Motif-based method [10], and convolutional matching pursuit (CMP) dual-dictionary method [11], etc. These methods localize the defect using template-matching approach, requiring use of a suitable template and precise alignment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is statistically shown that the accuracy of manual detection is only from 60 to 75%. Moreover, the detection rate is often influenced by many emotional factors and detection conditions [2, 3]. Therefore, in order to increase the detection rate as well as to reduce the labour cost, it is necessary to develop an automated detection technology to accomplish high‐accurate and low‐cost fabric defect detection (FDD) [4].…”
Section: Introductionmentioning
confidence: 99%